An approach to the calculation of multilayer magnetic shielding using artificial neural network - Koroglu, S.; Umurkan, N.; Kilic, O.; Attar, F. (ELSEVIER, 2009)
The electromagnetic interference has many undesired effects to the office equipments and the performance of technological devices. Therefore, electrical devices should have field protection mechanism against magnetic fields. The shielding mechanism prevents external magnetic field emitted from the device to the vicinity area. This work attempts to apply artificial neural network in order to estimate shielded magnetic field for multilayer shielding application. The multilayer magnetic shielding performances of cylindrical shaped ferromagnetic shields under extremely low frequency are investigated. For this purpose, three different ferromagnetic materials in cylindrical shape are chosen for magnetic shielding. The shielding performances of these materials are measured and a selected set of data is used to train and test an artificial neural network. The proposed neural network model achieves an intelligent decision for the shielded magnetic field level based on distance, unshielded magnetic field value, number of shield layer and skin-depth of the shield. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Multilayer magnetic shielding; Neural network; Shielded field estimation; Computer Science